The Permanent Deformation Criterion of Unbound Granular Materials (UGMS) Layer - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (International Committee on Road & Airfield Pavement Technology (ICPT), 2011)
This paper reports the permanent deformation evaluation of crushed rock under repeated cyclic loading triaxial tests performed at different stress levels, in order to improve permanent deformation prediction for unbound granular materials (UGMs). Road rutting is the main cause of damage inflexible pavements which the most explanation is crushed rock still not obviously understanding about plastic deformation under service load. The permanent deformation that accumulates under the repeated loading can normally describe and define the types of responses. Theoretical approach of the UGMs permanent deformation used to describe the behavior of tested materials subject to repeated cyclic loading triaxial (RLT) tests by macro-mechanical observations of the UGMs response. The plastic limit is able to use predict the accumulated plastic deformation in the UGMs layer of road pavement or whether deterioration will be unacceptable. Tested material will be determined the limit of working stress level and the plastic deformation should be considered in this behavior. The paper presents permanent deformation prediction.